HUMAN TEETH APATITE MICROANALYSIS: DETERMINATION OF INDIVIDUALS’ AGE AND SEX FOR FORENSIC APPLICATIONS - Caron de Souza, Pamela; Valle Pinto-Coelho, Cristina; Tavares Marques, Gisele; de Filippis Alfaro, Lorena; Gomes da Silva, Thiago; Cavallari, Marcella Luiza; Lamarão, Claudio Nery; Evangelista Lagoeiro, Leonardo (Boletim Paranaense de Geociências, 2022)
Teeth, as well as other hardened body structures, are extremely useful in forensic analysis and identification of human remains. Due to their compositional characteristics, they are preserved over time and are resistant to high temperatures, making them a fundamental in contexts where individuals cannot be identified visually or by other means. Current studies of the crystal structure properties of human dental apatite (hydroxyapatite) have been conducted and highlight its decrease in function of age, but fail in establishing a mathematical relationship between these parameters. This study performed X-ray diffractometry (XRD) and electronic microprobe analyses (EPMA) in 29 teeth aiming at determining an age and sex criteria of identification based on the crystalline reticulum’s parameters results, crystallite size and chemical composition of dental apatite. Through these methods it was possible to recognize that decreasing contents of calcium correlate to the formation of mineral phases that alter the original dental composition, causing a decrease in crystallinity with advancing age, and most importantly, it was possible to verify, as a result of a theoretical model, here proposed, that crystallinities values are not absolute, but a spectrum for a certain age: where permanent non-third molar vary between 20 and 45 µm, with a range of for the same age; deciduous teeth between 50 and 57 µm, with a range of for the same age and third-molar teeth, above 60 µm.